1999
DOI: 10.1038/sj.hdy.6886020
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of individual inbreeding coefficients and pairwise relatedness in a population of Mimulus guttatus

Abstract: In order to infer population structure at the individual level, we estimated individual inbreeding coe cients and examined the relationship between geographical distance and genetic relatedness from polymorphic microsatellite data for a population of Mimulus guttatus that has an intermediate sel®ng rate. Expected heterozygosities for ®ve microsatellites ranged from 0.79 to 0.93. The population inbreeding coe cient was calculated to be 0.19 (SE 0.023). A method-of-moments estimator developed by Ritland (1996b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 40 publications
7
71
0
Order By: Relevance
“…Of course, the evolutionary relevance of C AD and V DI depends not only on their magnitudes, but also on the level of inbreeding in the population. M. guttatus is a mixed mating species and the estimated selfing rate varies from 0 to 0.75 among populations (Ritland and Ganders, 1987;Willis, 1993;Awadalla and Ritland, 1997;Sweigart et al, 1999). As a consequence, we expect the nonadditive components to impact substantially evolutionary change in some populations but make only a minor contribution in others.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the evolutionary relevance of C AD and V DI depends not only on their magnitudes, but also on the level of inbreeding in the population. M. guttatus is a mixed mating species and the estimated selfing rate varies from 0 to 0.75 among populations (Ritland and Ganders, 1987;Willis, 1993;Awadalla and Ritland, 1997;Sweigart et al, 1999). As a consequence, we expect the nonadditive components to impact substantially evolutionary change in some populations but make only a minor contribution in others.…”
Section: Discussionmentioning
confidence: 99%
“…The well-studied IM population consists of small-flowered, diminutive annuals that live on Iron Mountain, in Oregon's western Cascades (Willis 1993). These plants are predominantly outcrossing (Willis 1993;Sweigart et al 1999) and have a short period of growth and reproduction, with germination occurring in either the fall or spring, flowering occurring over a 3-to 5-week period in June through early July. All plants at this site die by mid-July.…”
Section: Methodsmentioning
confidence: 99%
“…The species is mixed mating, the estimated selfing rate varies from 0 to 0.75 among populations, and it may be annual, winter annual, or perennial (Ritland and Ganders 1987;Willis 1993;Awadalla and Ritland 1997;Sweigart et al 1999). Previous genetic studies have demonstrated substantial genetic variation in floral traits (Carr and Fenster 1994;Robertson et al 1994) and inbreeding depression in fitness components (Dole and Ritland 1993;Willis 1993;Latta and Ritland 1994;Willis 1999a,b;Carr and Dudash 1996;Dudash and Carr 1998).…”
Section: Study Species and Source Populationmentioning
confidence: 99%